The da vinci code / Dan Brown; Penerjemah, Ingrid Dwijani Nimpoeno; Editor, Esti Budihabsari dan Andityas Prabantoro - BROWN, Dan; INGRID Dwijani Nimpoeno; ESTI Budihabsari; ADITYAS Prabanto (Bentang, 2014)
678 hlm. ; 18 cm.